2020
DOI: 10.1080/13669877.2020.1806911
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced threat or therapeutic benefit? Risk and benefit perceptions of human gene editing by purpose and heritability of edits

Abstract: Public discourse and deliberation are key to developing socially responsible and acceptable human gene editing research and applications. Researchers have raised concerns, however, that discourse about heritable gene edits, especially for non-therapeutic (or enhancement) purposes, might negatively bias public opinion of applications, including non-heritable edits to cure or prevent disease. Yet limited research exists examining how information about different gene editing applications elicits different percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…To obtain results, we conducted a hierarchical ordinary least squares (OLS) regression where the independent variables were entered into blocks according to their assumed causal order [Cohen, Cohen, West & Aiken, 2003]. During data collection, all participants were randomly assigned to five experimental conditions, as part of a separate study [Howell et al, 2022]. Because the experimental manipulations were not of primary interest, they are not reported here but their effects were controlled by including dummy variables within the models.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain results, we conducted a hierarchical ordinary least squares (OLS) regression where the independent variables were entered into blocks according to their assumed causal order [Cohen, Cohen, West & Aiken, 2003]. During data collection, all participants were randomly assigned to five experimental conditions, as part of a separate study [Howell et al, 2022]. Because the experimental manipulations were not of primary interest, they are not reported here but their effects were controlled by including dummy variables within the models.…”
Section: Resultsmentioning
confidence: 99%
“…Vasquez-Loarte et al analyzed the perspective of patients with hemophilia and concluded that more research needs to be done for patients to favor such therapy due to the uncertainty surrounding it [ 34 ]. In the US, Howell et al conducted an online survey of 1,600 adults and revealed that people view the therapeutic benefits positively, but do not like the risk of heritable human genomic editing that can be passed down to future generations [ 35 ]. Shozi analyzed the argument centered around human dignity from an African perspective and concluded that the Ubuntu perspective supports therapeutic human genomic editing only if the child’s autonomy is maintained [ 36 ].…”
Section: Reviewmentioning
confidence: 99%
“…The consensus was that the mainstay treatment is preferred as it is more established from both a safety and efficacious standpoint [ 34 ]. Expanding to more general uses, one study sent a survey to 1,600 United States adults to assess the perspective for therapeutic versus enhancement use and whether it was for heritable versus non-heritable applications [ 35 ]. Irrespective of if genome editing would be used for heritable or non-heritable applications, the majority had endorsed it with favor if it were strictly therapeutic in nature [ 35 ].…”
Section: Reviewmentioning
confidence: 99%